Directions of Polderization in the Middle Basin of the Odra River = Kierunki polderyzacji dorzecza Środkowej Odry - Golik, Dawid; Gortych, Marta; Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As an effective way of flood prevention it is widely accepted to construct flood embankments. These structures are getting bigger as the river changes from meandring to successive development of floodplain and narrowing the embankment. Meanwhile, it is worth returning old solutions and reactivating old floodplain polders.
Keywords: polder; flood; retention; powódź; retencja